Not all sprawl - Evolution of employment centers in Los Angeles, 1980-2000 - Genevieve Giuliano; Christian Redfearn (European Regional Science Association (ERSA), 2005)
Are contemporary metropolitan regions becoming more dispersed? The collective set of urban models tells us two stories. The first is that changes in the structure of the economy, ever faster and cheaper information and communications technologies, and the dispersion of the labor force have broadened the scope of agglomeration economies. Hence employment will continue to decentralize. The alternative story argues that heavy reliance on face-to-face communication in the information economy, economies of scale and scope in infrastructure, and historical path dependence in urban spatial patterns suggest that highly localized agglomeration economies continue to exist. The purpose of our research is to establish robust empirical evidence that can help clarify the debate over the evolution of economic activity within a metropolitan area and provide the data that can be used to test the implications of many of the models that speak to urban dynamics. We examine changes in employment patterns in the Los Angeles region, from 1980 to 2000. As a rapidly growing, prototypically polycentric region, Los Angeles provides an interesting case study of spatial evolution. Using data from 1980, 1990 and 2000, we identify employment centers and describe spatial trends in the pattern of employment inside and outside these centers. Our findings point to three trends in the evolution of the topography of employment. First, there is a remarkable degree of stability in the system of centers. While a small number of centers appear and disappear, the large majority of centers are evident throughout the three sample periods. This stability does not mean that the distribution of employment has been static, however. The second trend is a marked spread in the average distance of jobs from the traditional core: the average job in 2000 was significantly further from downtown than in 1980. This decentralization is not simply dispersion, but rather both deconcentration and concentration. That is, while the most rapid job growth has occurred in the outer suburbs, suburban employment centers have become more numerous, larger and more concentrated. These trends appear to defy simple models of urban evolution and call for a more nuanced understanding of the dynamics underlying these trends.
Keywords: 330